Neuropsychiatric systemic lupus erythematosus in elderly people: a case series. Issue 12 (December 1992) - Dennis, M S; Byrne, E J; Hopkinson, N; Bendall, P
Abstract : Five elderly patients presenting with neuropsychiatric systemic lupus erythematosus were referred to the sectorised psychiatry service of the department of health care of the elderly. They represented 2% of patients admitted over a period of two years. Two patients presented with a subacute confusional state, two with dementia, and one with depression. Three patients responded well to treatment. This suggests that systemic lupus erythematosus (SLE) is more common in elderly people than was originally thought and is a potentially treatable cause of organic brain disorder. The absence of reports of elderly patients with SLE is likely to be due to the continued application of the American Rheumatism Association's revised 1982 classification criteria, which are inappropriate for this population.